Volunteerism and legislation: A guidance note - IPU, UN (2004)
The Note was prepared following extensive consultations, primarily through a questionnaire, with parliamentarians from all regions, North and South, volunteer-involving organisations and Red Cross and Red Crescent National Societies. Supplementary information was obtained from research papers, Internet searches, and face-to-face and phone interviews.